Pengaruh Promosi Media Sosial Terhadap Minat Berkunjung Wisatawan Pada Wisata Hiu Paus - Moh. Thoriq Hamid; Zainal Abidin Umar (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine how the influence of social media promotion on tourist interest in visiting the Botubarani Whale Shark tourist attraction in Bone Bolango, Gorontalo Province. This study involved 96 respondents who were determined using a purposive sampling method, with the criteria that respondents had seen or received information about the Botubarani Whale Shark attraction through social media. The approach in this study used a quantitative method with data collection techniques through distributing questionnaires. The data analysis technique was simple linear regression with the Statistical Program for Social Science (SPSS) version 21. The result shows that social media promotion had a positive effect on tourist interest in visiting. The results of the R Square determination coefficient analysis were 0.547 or 54.7%, which means that the variable of tourist interest in visiting can be explained by social media promotion, while the other 45.3% is explained by other variables outside this study, such as tourist attractions, facilities, destination image, and tourist experience. The t-test results obtained a t-count value of 10.645 with a significance value of 0.000 which shows that social media promotion has a significant effect on tourists' interest in visiting the Botubarani Whale Shark.